Strategi Penerapan Ice Breaking dalam Mengatasi Kebosanan Siswa pada Pembelajaran IPS di SMP N 26 Kabupaten Tebo - Devi Asri Purnama; Slamet Rianto; Yuherman (Geography Education Study Program, Universitas Kanjuruhan Malang, 2023)
This research is motivated by the problem of student boredom in the learning process at school. The learning that is carried out is still dominated by listening to the teacher's explanation in class, taking notes or summarizing the material. Learning that only uses books will of course make students bored and not interested in following the ongoing lessons. This study aims to find out whether the application of ice breaking can overcome student boredom in the learning process at SMPN 26 Tebo District. The method used in this study is the experimental quantitative method. Sampling was done by random sampling technique. The population in this study was class VII with a sample of 50 people divided into 25 students in the control class and 25 students in the experimental class. The instruments used were tests and questionnaires. Data collection techniques carried out were tests, questionnaires, documentation. The data analysis technique used in this study is the Normality Test, Homogeneity Test, then proceed with hypothesis testing using the t-test. Based on the analysis of normality test data for all pretest and posttest experimental and control group data, it shows that the significant value of Kolmogorov-Smirnov and Shapiro-Wilk is > 0.05, which means that the data is normally distributed. .05 so that it can be concluded that the data is homogeneous. Then the results of data analysis hypothesis testing using the t-test with a significant value of 0.001. So it can be concluded that the application of ice breaking can overcome student boredom in social studies learning at SMPN 26 Tebo Regency with a significance value of 0.001 <0.05. Thus Ha is accepted.